Posaconazole prophylaxis – impact on incidence of invasive fungal disease and antifungal treatment in haematological patients. Issue 6 (26th May 2013) - Peterson, Lisa; Ostermann, Julia; Rieger, Heidi; Ostermann, Helmut; Rieger, Christina Theresa
Summary: Since two large‐scale, randomised studies on posaconazole prophylaxis have demonstrated a clear benefit for patients at high risk for contracting invasive fungal disease (IFD), posaconazole prophylaxis has been adopted as standard of care for this patient collective. Several years on from implementation at our institution, we wanted to evaluate its impact on the incidence and use of empirical antifungal therapy in a real‐life setting. We analysed retrospectively incidence and severity of IFD in high‐risk patients with prophylaxis, using a historical cohort as comparator. A total of 200 patients had either received the extended spectrum triazole posaconazole in prophylactic dosage of 200 mg tid or empirical antifungal therapy. Disease events were analysed by application of the revised EORTC/MSG definitions for IFD. Before posaconazole prophylaxis, we recorded 57/100 cases of IFD which was reduced to 28/100 with prophylaxis. The empirical use of antifungal drugs was reduced to 41% from 91% in the non‐prophylaxis cohort. Furthermore, we observed a shift in the categorisation of IFD according to EORTC/MSG criteria. Our data suggest that posaconazole was effective in reducing the rate and probability of invasive fungal disease in high‐risk patients.